FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KECEMASAN IBU HAMIL MENJELANG PERSALINAN DI RUMAH SAKIT BHYANGKARA AMBON - Asriaty Dinopawe; Hesti Nurlatu (Pasapua Health Journal, 2020)
Introduction: Childbirth is a transitional time from a period before having children until the fetus is in the womb and then born. This radical change in status will require psychological preparation. The delivery process often results in psychological aspects, giving rise to various psychological problems for pregnant women, one of which is anxiety. Every pregnant woman will usually experience fear of things she does not know, such as not being ready to give birth, labor not according to schedule, bad experiences from relatives or friends about childbirth. Methods: This study used a descriptive analytic research design using a cross sectional approach. The sample in this study were all third trimester pregnant women who checked their pregnancies at the KIA polyclinic at Bhayangkara Ambon Hospital as many as 169 people, pregnant women. Results: showed that of the 138 respondents who had sufficient knowledge, there were 86.5% whose anxiety for pregnant women was not anxious, while of the 31 respondents who had less knowledge, there were only 15.4% of respondents who did not support their husbands and 96.4% had good support. Statistical value test p-value = 0.05. Conclusion: it was concluded that there is a relationship between knowledge, husband support and parity with anxiety in third trimester pregnant women before delivery at Bhayangkara Ambon Hospital. Suggestion: it is expected to increase knowledge, support husbands for pregnant women about the level of anxiety in facing childbirth. Bhayangkara Ambon Hospital can provide counseling to pregnant women and their families/husbands about anxiety before childbirth.